Alcohol dispersion of conductive polyethylenedioxythiophene, its manufacturing method and use
Patent Information
- Application Number
- JP2024545825
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-31
- Filing Date
- 2022-10-11
- Publication Date
- 2025-02-26
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
を有する。 (1)本発明では、PSSの代わりにアルコールに分散可能な高フッ素化スルホン酸イオンポリマーを対アニオンとして使用し、PEDOTアルコール分散液を調製した。合成過程におけるパーフルオロスルホン酸イオンポリマーとチオフェンモノマーの仕込み比を制御することにより、異なる導電率のアルコール分散液が得られ、弱酸性を有し、ZnOなどの金属酸化物及び腐食することがなく、高浸潤性を有し、界面活性剤を添加する必要がなく、スピンコート、ブレードコート、スリットコートなどの塗布プロセスにより均一な導電性薄膜を製造することができ、従来の水分散液に存在する吸湿性の問題が解決され、従来の導電性ポリエチレンジオキシチオフェン水分散液(PEDOT:PSS)が比較的大きい表面張力により疎水性表面に均一に塗布できないとの問題が克服される。 (2)本発明で提供される導電性ポリエチレンジオキシチオフェンアルコール分散液は、弱酸性または中性であるため、従来の水分散液の強酸性による金属酸化物、金属電極及び金属ナノワイヤに対する腐食の問題を解決する一方、アルコール分散液は、比較的小さい表面張力を有するため、任意の表面に塗布されて加工して均一な導電性薄膜を製造することができる。 (3)本発明は、合成プロセスが簡単で、異なるベース及び異なる種類の光電デバイス、熱電デバイス、エレクトロクロミックフィルム及び帯電防止コート層に使用することができ、応用の可能性は広い。
Smart Images

Figure 2025505453000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of photoelectric materials, in particular to an alcohol dispersion of conductive polyethylenedioxythiophene, its preparation method and use. [Background technology]
[0002] The conductive polymer poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) has the advantages of high electrical conductivity, ionic conductivity, high optical transparency and solution processability, and can be widely used in antistatic coating layers, optoelectronic devices, power storage devices and bioelectronic devices. PEDOT is an insoluble polymer. The water-soluble anionic polymer PSS has two actions: (1) it electrostatically interacts with the positively charged PEDOT as a counter anion; and (2) it forms a stable aqueous dispersion as a dispersant. Currently, PEDOT:PSS aqueous dispersions with different electrical conductivities are being developed by Heraeus in Germany and Agfa in Belgium. However, PEDOT:PSS aqueous dispersions have the following disadvantages: (1) they have low wettability. Water has a relatively high surface tension (72 mN m -1 / 25°C), it is difficult to form a uniform film when a PEDOT:PSS aqueous solution is applied to a hydrophobic surface with a relatively low surface energy. (2) Acidity. The PEDOT:PSS aqueous dispersion has a pH value of 1.5-2.5, which can corrode materials such as metals and metal oxides. (3) Hygroscopicity. PSS is prone to absorbing water, and when a PEDOT:PSS thin film absorbs moisture, its electrical performance decreases and it is prone to oxidizing and corroding materials in other functional layers, causing a decrease in device performance and lifespan.
[0003] All of the above problems are related to the dispersion solvent water. PSS has a very high dissociation rate in water, which causes high acidity and hygroscopicity, and the large surface tension of water causes low wettability of PEDOT:PSS aqueous dispersions. Compared to water, alcohol has a low surface tension (e.g., the surface tension of methanol and ethanol is 22-23 mN m).-1 (The dissociation rate of acids in alcohol is much slower than that in water [Proc.R.Soc.Lond.A 1929,126,84-106]. Therefore, alcohol-dispersible PEDOT is advantageous for improving wettability and reducing acidity, thereby improving device performance and stability. However, since the dispersion concentration of PSS in alcohol is less than 5 mg / mL, it is difficult to obtain a stable PEDOT:PSS alcohol dispersion when PSS is used as a counter anion. All of the PEDOT:PSS dispersions disclosed in the prior art are water or water / alcohol mixtures. Therefore, it is necessary to develop a stable alcohol-dispersible PEDOT solution.
[0004] For the above reasons, the prior art does not yet have a stable alcohol dispersion of conductive polyethylenedioxythiophene. Summary of the Invention
[0005] In response to the above-mentioned deficiencies or needs for improvement in the prior art, the present invention provides an alcohol dispersion of conductive polyethylenedioxythiophene. A highly fluorinated sulfonate ion polymer dispersible in alcohol is used as a counter anion instead of PSS to prepare a PEDOT alcohol dispersion. By controlling the ratio of perfluorosulfonate ion polymer and thiophene monomer in the synthesis process, alcohol dispersions with different electrical conductivity can be obtained. This alcohol dispersion has a weak acidity, is not corroded by metal oxides such as ZnO, has high infiltration, does not require the addition of surfactants, and can produce a uniform conductive thin film by coating processes such as spin coating, blade coating, and slit coating.
[0006] In order to achieve the above object, according to one aspect of the present invention, there is provided a conductive polyethylenedioxythiophene comprising a polyethylenedioxythiophene cation and a fluorinated sulfonate ion polymer counter anion, and having a structure represented by formula (I). [ka] In the formula, n represents the degree of polymerization of polyethylenedioxythiophene and is an integer of 2 to 100, p represents the degree of polymerization of the fluorinated sulfonic acid polymer and is an integer of 2 to 100, m is a real number of 1 to 20, x is 0 or 1, y is an integer of 1 to 5, and R is a hydrogen atom, a hydroxyl group, an alkyl group, an alkoxy group, a fluoroalkyl group, an ester group, a carboxyl group, a thioalkyl group, an aryl group, or a heteroaryl group.
[0007] In the formula (1) of the present invention, m is the average degree of polymerization. The polymer includes homogeneous polymer molecular structures having different degrees of polymerization. m is the number-average degree of polymerization obtained by averaging the number of molecules, and may be a non-integer.
[0008] Preferably, R is a hydrogen atom or a fluoroalkyl group.
[0009] Preferably, m in formula (1) is 4.5-10, x is 1, and y is 1-3.
[0010] According to another aspect of the present invention, there is provided a method for producing conductive polyethylenedioxythiophene, comprising dissolving a fluorinated sulfonate ion polymer and a thiophene monomer in a solvent to prepare a dispersion having a mass concentration of 1% to 30%, then adding an oxidizing agent to react with the dispersion to obtain a blue-black liquid, removing unreacted monomer and oxidizing agent by semipermeable membrane dialysis, and then centrifuging the liquid to obtain the conductive polyethylenedioxythiophene.
[0011] Preferably, the solvent is water or an alcohol.
[0012] Preferably, when the solvent is water, the oxidizing agent is a water-soluble oxidizing agent or an alcohol-soluble oxidizing agent; When the solvent is an alcohol, the oxidizing agent is an alcohol-soluble oxidizing agent; The water-soluble oxidizing agent includes at least one of iron(III) salts, persulfates, peroxides, V2O5, VOCl3, and SbCl5, and the alcohol-soluble oxidizing agent includes at least one of dibenzoyl peroxide and phosphomolybdic acid.
[0013] According to another aspect of the present invention, there is provided a method for producing an alcohol dispersion of conductive polyethylenedioxythiophene, comprising dispersing the conductive polyethylenedioxythiophene in an alcohol solution by ultrasonic waves to obtain an alcohol dispersion of conductive polyethylenedioxythiophene.
[0014] Preferably, the alcohol solution is one or a mixture of two or more of a fatty alcohol solution, a cycloaliphatic alcohol solution and an aromatic alcohol solution.
[0015] According to another aspect of the present invention, there is provided a method for producing an alcohol dispersion of conductive polyethylenedioxythiophene, comprising adding a fluorinated sulfonate ion polymer and a thiophene monomer to an alcohol solution to prepare a dispersion having a mass concentration of 1%-30%, then adding an oxidizing agent to react with the polymer to obtain a blue-black liquid, removing unreacted monomer and oxidizing agent by semipermeable membrane dialysis, and then obtaining an alcohol dispersion of conductive polyethylenedioxythiophene.
[0016] According to another aspect of the present invention, there is provided a method for producing a conductive polyethylenedioxythiophene dispersion in an alcohol, comprising the steps of: The uses include solar cells, light emitting diodes, electrochromic films, thermoelectric materials, antistatic coating layers, flexible electronic devices or stretchable elastomeric sensors.
[0017] Since anionic polymers are used as dispersants, the key to preparing PEDOT alcohol dispersions is to obtain a counter anionic polymer that can be dispersed in alcohol. However, the anionic polymers described in the prior art have very low dispersion concentrations in alcohol (<5 mg / mL) and cannot be used to prepare PEDOT alcohol dispersions. Further screening revealed that a certain type of highly fluorinated sulfonic acid ion polymer has two solubility parameters of 16.71-17.37 cal. 0.5 cm -1.5 and 9.61-10.08 cal. 0.5 cm -1.5 The former is due to the hydrophilic acid ion group, and the latter is due to the hydrophobic polytetrafluoroethylene group. The solubility parameters of the above two are respectively water (23.4 cal 0.5 cm -1.5 ) and ethanol (12.7 cal. 0.5 cm -1.5 ), the solubility parameter of the highly fluorinated sulfonic acid ion polymer is similar to that of PSS, and therefore the dispersion concentration in both water and alcohol is higher than 20 mg / mL. Therefore, in the present invention, a highly fluorinated sulfonic acid ion polymer dispersible in alcohol instead of PSS is used as a counter anion to prepare a PEDOT alcohol dispersion. By controlling the charge ratio of the perfluorosulfonic acid ion polymer and the thiophene monomer in the synthesis process, alcohol dispersions with different electrical conductivity were obtained. This alcohol dispersion has weak acidity, is not corroded by metal oxides such as ZnO, has high infiltration, does not require the addition of a surfactant, and can produce a uniform conductive thin film by coating processes such as spin coating, blade coating, and slit coating. In addition, since this anionic polymer has a large amount of hydrophobic -CF2- groups, the produced PEDOT thin film has high hydrophobicity. Therefore, the conductive polyethylenedioxythiophene alcohol dispersion can be used for hole transport layers and electrodes in photoelectric devices (e.g., solar cells, light-emitting diodes, photodetectors, etc.), antistatic coating layers, electrochromic devices, thermoelectric materials, bioelectronic devices, etc. From the above, the present invention has the following beneficial effects. (1) In the present invention, a highly fluorinated sulfonic acid ion polymer dispersible in alcohol was used as a counter anion instead of PSS to prepare a PEDOT alcohol dispersion. By controlling the ratio of perfluorosulfonic acid ion polymer and thiophene monomer in the synthesis process, alcohol dispersions with different electrical conductivity can be obtained, which have weak acidity, are not corroded by metal oxides such as ZnO, have high infiltration properties, do not require the addition of surfactants, and can produce uniform conductive thin films by coating processes such as spin coating, blade coating, and slit coating, solving the problem of hygroscopicity present in conventional aqueous dispersions, and overcoming the problem that conventional conductive polyethylenedioxythiophene aqueous dispersions (PEDOT:PSS) cannot be uniformly applied to hydrophobic surfaces due to their relatively large surface tension. (2) The conductive polyethylenedioxythiophene alcohol dispersion provided by the present invention is weakly acidic or neutral, and therefore solves the problem of corrosion of metal oxides, metal electrodes, and metal nanowires caused by the strong acidity of conventional aqueous dispersions. Meanwhile, the alcohol dispersion has a relatively small surface tension, and can be applied to any surface and processed to produce a uniform conductive thin film. (3) The present invention has a simple synthesis process, and can be used on different bases and in different kinds of photoelectric devices, thermoelectric devices, electrochromic films and antistatic coating layers, and has a wide range of application possibilities. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is a schematic structural diagram of conductive polyethylenedioxythiophene. [Diagram 2] FIG. 2 is a curve test diagram of absorptance and transmittance of the 46.1 nm PEDOT:F thin film prepared in Example 1. [Diagram 3] 3 shows the conductive performance test of the 46.1 nm PEDOT:F thin film prepared in Example 1. The left figure in Fig. 3 is the conductivity test, and the right figure in Fig. 3 is the resistance and its fitting curve test. [Figure 4]4 is a structure and test diagram of an inverted organic solar cell of Application Example 1. The left diagram of Fig. 4 is a schematic diagram of the device structure of an inverted organic solar cell, and the right diagram of Fig. 4 is a current density-voltage test diagram of the organic solar cell. [Diagram 5] 5 is a structure and test diagram of a positive-type organic solar cell of Application Example 2. The left diagram of Fig. 5 is a schematic diagram of the device structure of a positive-type organic solar cell, and the right diagram of Fig. 5 is a current density-voltage test diagram of the organic solar cell. [Figure 6] The structure and test diagram of the fully solution-processed organic solar cell of Application Example 3. The left diagram of Fig. 6 is a schematic diagram of the device structure of the fully solution-processed organic solar cell, and the right diagram of Fig. 6 is a current density-voltage test diagram of the organic solar cell. [Figure 7] FIG. 11 is a temperature difference-voltage curve diagram of a thermoelectric device according to Application Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] In order to clarify the purpose, technical means and advantages of the present invention, the present invention will be described in more detail below with reference to the drawings and examples. Note that the following specific examples are merely for the purpose of interpreting the present invention and are not intended to limit the present invention. Furthermore, the technical features according to each embodiment of the present invention described below can be combined with each other as long as they are not inconsistent with each other.
[0020] Working Example The conductive polyethylenedioxythiophene contains a polyethylenedioxythiophene cation and a fluorinated sulfonate ion polymer counter anion, and has a structure represented by the following formula (I). [ka] In the formula, n represents the degree of polymerization of polyethylenedioxythiophene and is an integer of 2 to 100. p represents the degree of polymerization of the fluorinated sulfonic acid polymer and is an integer of 2 to 100, m is a number of 1 to 20, x is 0 or 1, y is an integer of 1 to 5, and R is a hydrogen atom, a hydroxyl group, an alkyl group, an alkoxy group, a fluoroalkyl group, an ester group, a carboxyl group, a thioalkyl group, an aryl group, or a heteroaryl group. Preferably, R is a hydrogen atom or a fluoroalkyl group. Preferably, in formula (1), m is 4.5-10, x is 1, and y is 1-3.
[0021] Example 1 Conductive polyethylenedioxythiophene alcohol dispersion is synthesized by the following method. 2 mL of 10 wt% perfluorosulfonic acid ion polymer (PFI; the molecular weight of the monomer is 1094 g / mol, and its molecular structure is represented by formula (II)) aqueous solution and 20 μL of 3,4-ethylenedioxythiophene monomer are added to 6 mL of deionized water and stirred at room temperature for 1 h. After it becomes a milky white liquid, the oxidizing agent is slowly dropped. The oxidizing agent is prepared by dissolving 60.75 mg of ferric chloride (FeCl3) in 3 mL of deionized water. After adding the oxidizing agent, the milky white liquid gradually begins to turn blue, and after reacting for 12 h, it becomes a blue-black liquid. The blue-black liquid is put into a semipermeable membrane and small molecular impurities and excess oxidizing agent are removed by dialysis, and after 18 h, the liquid is taken out and centrifuged at high speed at 10,000 rpm to obtain a blue-black solid. The blue-black solid was placed in an alcohol solvent and subjected to ultrasonic cell disruption treatment for 10 h, after which a conductive polyethylenedioxythiophene alcohol dispersion (PEDOT:F) was obtained. The mass fraction of this conductive polyethylenedioxythiophene alcohol dispersion was 1.3-1.8 wt.%. [ka] Here, p is an integer from 1 to 20.
[0022] The PEDOT:F solutions were processed by spin coating to form films, and the resulting films were dynamically spin-coated onto clean glass at spin-coating speeds of 1000 rpm, 2000 rpm, 3500 rpm, and 5000 rpm, respectively. After spin-coating, the films were annealed at 100°C for 5 minutes, and the thicknesses of the resulting PEDOT:F thin films were 53.0 nm, 46.1 nm, 35.8 nm, and 25.2 nm, respectively.
[0023] Taking the PEDOT:F thin film with a thickness of 46.1 nm as an example, its absorptance and transmittance curves are shown in FIG. 2, and the work function was measured to be 5.4 eV.
[0024] The conductivity was calculated using this 46.1 nm thin film. As shown in Figure 3, the left figure in Figure 3 is the conductivity test, and the right figure in Figure 3 is the resistance and its fitting curve test. The calculated thin film conductivity is 5.4 × 10 -2 It was S / cm.
[0025] Example 2 Conductive polyethylenedioxythiophene alcohol dispersion is synthesized by the following method. 10mL of 20wt% perfluorosulfonic acid ion polymer (PFI, monomer molecular weight is 1094g / mol) water-alcohol mixed solution, 0.6g of 3,4-ethylenedioxythiophene monomer oxidant, and 1.05g of dibenzoyl peroxide (BPO) oxidant were added to 10mL of ethanol. After stirring continuously for 48h, a blue-black liquid was obtained. In the post-treatment stage, the blue-black liquid was placed on a semipermeable membrane and dialyzed. The dialysis solvent was a mixed solution with a volume ratio of ethanol:water = 1:1. Low molecular weight impurities and excess oxidant were removed by dialysis for 24h to obtain an alcohol dispersion. The mass fraction of the produced conductive polyethylenedioxythiophene alcohol dispersion was 1.3-1.8wt.%.
[0026] The PEDOT:F solutions were processed by spin coating to form films, and the resulting films were dynamically spin-coated onto clean glass at spin-coating speeds of 2000 rpm, 3500 rpm, and 5000 rpm, respectively. After spin-coating, the films were annealed at 100°C for 5 minutes, and the thicknesses of the resulting PEDOT:F thin films were 37.0 nm, 28.4 nm, and 18.2 nm, respectively. Taking the 37.0 nm-thick PEDOT:F thin film as an example, the work function was measured to be 5.3 eV, and the electrical conductivity was measured to be 4.2×10 -3 It was S / cm.
[0027] Example 3 In this example, the production method was the same as that of Example 1, except that the structure of the perfluorosulfonic acid ion polymer was represented by the following formula (III). [ka]
[0028] Example 4 In this example, the production method was the same as that of Example 1, except that the structure of the perfluorosulfonic acid ion polymer was represented by the following formula (4). [ka]
[0029] Application examples
[0030] Application Example 1 The thin film produced using the conductive polyethylenedioxythiophene alcohol dispersion liquid described in Example 1 was used as it was as the hole transport layer of an organic solar cell having an inverted structure. The device structure of the inverted organic solar cell is glass / ITO / ZnO / PM6:Y6:PCBM / PEDOT:F / Ag, as shown in the left diagram of Figure 4. Here, ITO glass is the cathode layer, ZnO is the electron transport layer, PM6:Y6:PCBM is the photoactive layer, PEDOT:F is the hole transport layer, and Ag is the anode layer. The specific manufacturing method is as follows.
[0031] The cut indium tin oxide (ITO) glass, which is a transparent electrode, was ultrasonically cleaned in deionized water, acetone, and isopropanol for 15 minutes. A zinc oxide sol-gel solution was spin-coated on the cleaned ITO glass piece at 3000 rpm / min, and then heated at 200°C for 15 minutes. A PM6:Y6:PCBM solution (total concentration 15.4 mg / mL, mass ratio 1:1.2; solvent is chloroform) was spin-coated on the above base at 2500 rpm / min, and then annealed at 100°C for 10 minutes. A conductive polyethylenedioxythiophene alcohol dispersion was spin-coated on the active layer at 3000 rpm / min, and then annealed at 100°C for 5 minutes. The thin film produced using the conductive polyethylenedioxythiophene alcohol dispersion had a conductivity of 5.4×10 -2 Finally, the device was transferred into a deposition chamber where the vacuum pressure was 5×10 -7 After reaching below Torr, a 100 nm silver electrode was evaporated.
[0032] The current density-voltage of the fabricated organic solar cell is shown in the right figure of Figure 4. Voltage is the voltage, current density is the current density, and open circuit voltage is V OC = 0.85V, and the current density is J SC =25.40mA / cm 2 , the fill factor was FF=0.76 and the efficiency was PCE=16.40%.
[0033] Application Example 2 The thin film produced using the conductive polyethylenedioxythiophene alcohol dispersion liquid described in Example 1 was used as it was as a hole transport layer of an organic solar cell having a positive type structure. Fabrication of positive-type organic solar cells The device structure of the positive-type organic solar cell is glass / ITO / PEDOT:F / D18-Cl:N3:PCBM / PDINN / Ag, as shown in the left diagram of Figure 5. Here, ITO glass is the anode layer, PEDOT:F is the hole transport layer, D18-Cl:N3:PCBM is the photoactive layer, PDINN is the electron transport layer, and Ag is the cathode layer. The specific manufacturing method is as follows.
[0034] The cut indium tin oxide (ITO) glass transparent electrodes were ultrasonically cleaned in deionized water, acetone, and isopropanol for 15 minutes. Conductive polyethylenedioxythiophene alcohol dispersion (PEDOT:F) was spin-coated onto the cleaned ITO glass pieces at 3000 rpm / min, and then heated at 100°C for 5 minutes. The thin film fabricated using the conductive polyethylenedioxythiophene alcohol dispersion had a conductivity of 5.4×10 -2 The ZnO / cm2O2 concentration was 1.0 S / cm and the work function was 5.4 eV. A D18-Cl:N3:PCBM solution (total concentration 15 mg / ml, mass ratio 1:1.4:0.1; solvent was chloroform) was spin-coated on the base at 4000 rpm / min (no annealing). A PDINN solution (total concentration 1 mg / mL; solvent was methanol) was spin-coated on the active layer at 3000 rpm / min (no annealing). Finally, the device was transferred into a deposition chamber, where a vacuum pressure of 5×10 -7 After reaching below Torr, a 100 nm silver electrode was evaporated.
[0035] The current density-voltage of the fabricated organic solar cell is shown in the right figure of Figure 5. Voltage is the voltage, current density is the current density, and open circuit voltage is V OC = 0.85V, and the current density is J SC =27.54mA / cm 2 , the fill factor was FF=0.75, and the efficiency was PCE=17.67%.
[0036] Application Example 3 The thin film prepared using the conductive polyethylenedioxythiophene alcohol dispersion described in Example 1 was directly used as the hole transport layer for a fully solution processed organic solar cell. Fabrication of fully solution-processed organic solar cells The fully solution-processed organic solar cell device is glass / Ag NWs / PEI-Zn / PM6:Y6:PCBM / PEDOT:F / Ag NWs, as shown in the left diagram of Figure 6. Here, glass is the base, silver nanowires (Ag NWs) are the cathode layer, PEI-Zn is the electron transport layer, PM6:Y6:PCBM is the photoactive layer, PEDOT:F is the hole transport layer, and Ag NWs is the anode layer. The specific fabrication method is as follows:
[0037] The cut glass was ultrasonically cleaned in deionized water, acetone, and isopropanol for 15 minutes. The cleaned glass pieces were blade-coated with an ethanol dispersion of Ag NWs with a concentration of 10 mg / mL. The blade coating substrate temperature was 35°C, the blade coating speed was 10 mm / s, and the slit width was 100 μm. The blade coating was repeated multiple times until the sheet resistance of the Ag NWs reached 20 Ω / sq, and then the Ag NWs were patterned by laser etching. The electron transport layer PEI-Zn was blade-coated on the patterned transparent electrode. The blade coating substrate temperature was 50°C, the blade coating speed was 10 mm / s, and the blade coating slit width was 150 μm. After the blade coating was completed, the sample was annealed at 150°C for 10 min. The active layer material PM6:Y6:PCBM (total concentration 15.4 mg / mL, mass ratio 1:1:0.2; solvent was chloroform) was blade-coated on the above electron transport layer. The blade coating speed was 20 mm / s, and the blade coating slit width was 150 μm. After the blade coating was completed, the sample was heated at 100° C. for 10 minutes in a glove box with a nitrogen gas atmosphere. PEDOT:F was blade coated onto the active layer as a hole transport layer. The blade coating conditions were a substrate temperature of 35° C., a blade coating speed of 10 mm / s, and a blade coating slit width of 150 μm. The thin film produced using the conductive polyethylenedioxythiophene alcohol dispersion had a conductivity of 6.8×10 -4 S / cm and a work function of 5.7 eV. Finally, a 2 mg / ml ethanol dispersion of Ag NWs was deposited as an anode layer on the PEDOT:F by flame deposition. The sheet resistance of the anode layer Ag NWs was 17 Ω / sq.
[0038] The current density-voltage of an organic solar cell is shown in the right figure of Figure 6. Voltage indicates the voltage, current density indicates the current density, and open circuit voltage is V OC = 0.84V, and the current density J SC =22.25mA / cm 2, the fill factor was FF=0.72, and the efficiency was PCE=13.45%.
[0039] Application Example 4 The thin film prepared using the conductive polyethylenedioxythiophene alcohol dispersion described in Example 1 was used to prepare an antistatic coating layer by a blade coating process. Specific manufacturing process of antistatic coating layer 2.5×7.5cm 2 The glass was ultrasonically cleaned with deionized water, acetone, and isopropanol for 15 minutes. The clean glass was placed on a blade coating table with a base temperature of 50°C, 50μL of conductive polyethylenedioxythiophene alcohol dispersion was taken, the slit width was set to 150μm, and the blade coating speed was set to 10mm / s. After one blade coating, it was heated at 100°C for 5 minutes. Under these blade coating conditions, the blade coating was performed 1-20 times in both directions. The thickness of the obtained thin film was adjustable between 40-10,000nm, and the sheet resistance was 10 3 -10 6 It was adjustable between Ω.
[0040] Application Example 5 A thermoelectric device was fabricated by spin coating using a thin film prepared using the conductive polyethylenedioxythiophene alcohol dispersion described in Example 1. Specific manufacturing process of thermoelectric devices 2.5×5cm 2 The glass was ultrasonically cleaned in deionized water, acetone, and isopropanol for 15 minutes. The conductive polyethylenedioxythiophene alcohol dispersion was spin-coated onto the cleaned glass piece at a rotation speed of 800 rpm, and after 45 seconds, it was heated at 100°C for 10 minutes. The deposition area of both ends of the thin film was 2.5 × 0.2 cm. 2 The metallic silver was used as the electrode.
[0041] The temperature difference-voltage curve of the fabricated thermoelectric device is shown in Figure 7. The Seebeck coefficient obtained by fitting the curve was 29.9 μV / K, and the power factor was 4.83 × 10 -3μW / mK 2 It was.
[0042] In summary, the conductive polyethylenedioxythiophene alcohol dispersion provided by the present invention has a simple synthesis process, is easy to process, and is highly compatible with various processing surfaces and processing processes. In addition, the thin film produced using the dispersion shows great applicability in device structures such as organic solar cells, antistatic coating layers, and thermoelectric devices.
[0043] As can be understood by those skilled in the art, the above description is only a preferred embodiment of the present invention, and does not limit the present invention. Any modifications, equivalent replacements and improvements made within the spirit and principle of the present invention should be included within the protection scope of the present invention.
Claims
1. A conductive polyethylenedioxythiophene comprising a polyethylenedioxythiophene cation and a fluorinated sulfonate ion polymer counter anion, the structure of which is represented by formula (I). 【Chemistry 1】 (In the formula, n represents the degree of polymerization of polyethylenedioxythiophene and is an integer from 2 to 100, p represents the degree of polymerization of the fluorinated sulfonic acid polymer and is an integer from 2 to 100, m is a real number from 1 to 20, x is 0 or 1, y is an integer from 1 to 5, and R is a hydrogen atom, a hydroxyl group, an alkyl group, an alkoxy group, a fluoroalkyl group, an ester group, a carboxyl group, a thioalkyl group, an aryl group, or a heteroaryl group.)
2. The conductive polyethylenedioxythiophene according to claim 1 , wherein R is a hydrogen atom or a fluoroalkyl group.
3. The conductive polyethylenedioxythiophene of claim 1, characterized in that in formula (1), m is 4.5-10, x is 1, and y is 1-3.
4. A method for producing conductive polyethylenedioxythiophene, comprising dissolving a fluorinated sulfonate ion polymer and a thiophene monomer in a solvent to prepare a dispersion having a mass concentration of 1% to 30%, adding an oxidizing agent to react with the resulting mixture, obtaining a blue-black liquid, removing unreacted monomer and oxidizing agent by semipermeable membrane dialysis, and then centrifuging the liquid to obtain the conductive polyethylenedioxythiophene according to any one of claims 1 to 3.
5. The method according to claim 4 , wherein the solvent is water or an alcohol.
6. When the solvent is water, the oxidizing agent is a water-soluble oxidizing agent or an alcohol-soluble oxidizing agent; When the solvent is an alcohol, the oxidizing agent is an alcohol-soluble oxidizing agent; The water-soluble oxidizing agent is a trivalent iron salt, a persulfate, a peroxide, V 2 O 5 , VOCl 3 and SbCl 5 6. The method according to claim 5, wherein the alcohol-soluble oxidizing agent comprises at least one of dibenzoyl peroxide and phosphomolybdic acid.
7. A method for producing an alcohol dispersion of conductive polyethylenedioxythiophene, comprising dispersing the conductive polyethylenedioxythiophene according to any one of claims 1 to 3 in an alcohol solution by ultrasonic waves to obtain an alcohol dispersion of conductive polyethylenedioxythiophene.
8. 8. The method according to claim 7, wherein the alcohol solution is one or a mixture of two or more of a fatty alcohol solution, an alicyclic alcohol solution, and an aromatic alcohol solution.
9. A method for producing an alcohol dispersion of conductive polyethylenedioxythiophene, comprising adding a fluorinated sulfonate ion polymer and a thiophene monomer to an alcohol solution to prepare a dispersion having a mass concentration of 1% to 30%, then adding an oxidizing agent to react with the polymer to obtain a blue-black liquid, and removing unreacted monomer and oxidizing agent by semipermeable membrane dialysis to obtain an alcohol dispersion of conductive polyethylenedioxythiophene.
10. Use of an alcohol dispersion of conductive polyethylenedioxythiophene, The use comprises a solar cell, a light emitting diode, an electrochromic film, a thermoelectric material, an antistatic coating layer, a flexible electronic device or a stretchable elastomeric sensor.
Citation Information
Patent Citations
Water-dispersible polythiophenes prepared with polymeric acid colloids
JP2006500463A
Water-dispersible polythiophene produced by polymer acid colloid
JP2006527277A
Non-aqueous dispersion comprising doped conductive polymer and colloid-forming polymeric acid
JP2007531807A
Sensors containing conductive polymer materials
JP2009533674A
Conductive polymer solution and process of manufacturing the same, and conductive polymer material and solid electrolytic capacitor
JP2014120603A